Factors Associated With Computer Vision Syndrome Complaints In Computer Science Students - Muhammad Ikrar Fadhillah; Muhammad Irwan Setiawan; Ihya Hazairin Noor; Mufatihatul Aziza Nisa; Fahrini Yulidasari (Lambung Mangkurat University, 2023)
Computer Vision Syndrome (CVS) has a global prevalence of 60%-90% among computer users where the total number of sufferers is estimated to reach > 60 million individuals per year and continues to appear one million new cases in the world. Based on the results of preliminary studies conducted on Computer Science students FMIPA ULM, it is known that the duration of computer use in a day for all respondents (100%) is >4 hours, this causes CVS sufferers among students to increase. The purpose of this study is to analyze the correlation of eye visibility, duration of computer use, and length of rest to CVS complaints in students majoring in computer science. The study used a cross sectional quantitative design with a population of 193 students and a sample of 72 taken through proportional random sampling. The research instrument used a questionnaire adapted from previous research for the variables of duration of computer use, length of rest, and CVS complaints, while the eye visibility variable used a tape meter. The results of Chi-Square testing showed that there was a correlation between eye distance (p-value = 0.018), duration of computer use (p- value = 0.002), and duration of rest (p-value = 0.001) with CVS complaints. Students are advised to adjust their eye distance with a computer screen as far as 50-100cm, take a break for 10 minutes when working in front of a computer for 1 hour, and adjust work patterns so that they are not long in front of the computer.